Triple-layer remote phosphor geometry: an excellent selection to improve the optical properties of white light-emitted diodes - Thuc Minh Bui; My Hanh Nguyen Thi; Nguyen Doan Quoc Anh; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2023)
High performance white-light-emitting diodes (WLEDs) have been the goal of recent research on phosphor-in-glass (PiG) devices. In this paper, we introduce a configuration of WLED that achieves high color rendering index (CRI), and correlated color temperature with the addition of Zn2SiO4:Mn2+, As5+ and YAl3O4B12:Eu3+. The technique is lower the temperature during the creation process of phosphor in glass and control the consistent thickness in between 0.5 to 0.7 mm to yield high color quality PiG, high CRI above 80 WLEDs, and extend the color temperature range to 3,900 to 5,300 K. The consistent heat generation combined with extraordinary CRI for PiG prove that low temperature sintering has the potential to create WLEDs with advanced quality. The improved WLEDs can be utilized in many high-demand lighting fields such as chromatic examination, medical analysis, and aesthetic lighting.